2014
DOI: 10.1097/ccm.0000000000000655
|View full text |Cite
|
Sign up to set email alerts
|

Critical Cerebral Perfusion Pressure at High Intracranial Pressure Measured by Induced Cerebrovascular and Intracranial Pressure Reactivity

Abstract: Critical cerebral perfusion pressure of 50 mm Hg was accurately determined by induced intracranial pressure reactivity and induced cerebrovascular reactivity, whereas the static method failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…These measurements of perfusate flow confirm adequate and physiological perfusion of the brain regions examined and indicate that with a saline‐based perfusion fluid less viscous than blood, adequate perfusion can be maintained at pressures (40–70 mm Hg) close to the critical cerebral perfusion pressure of 50 mm Hg measured in the rat by Bragin et al . ().…”
Section: Discussionmentioning
confidence: 97%
“…These measurements of perfusate flow confirm adequate and physiological perfusion of the brain regions examined and indicate that with a saline‐based perfusion fluid less viscous than blood, adequate perfusion can be maintained at pressures (40–70 mm Hg) close to the critical cerebral perfusion pressure of 50 mm Hg measured in the rat by Bragin et al . ().…”
Section: Discussionmentioning
confidence: 97%
“…We subsequently showed that the critical CPP of the cerebral circulation obtained by increasing ICP was accurately identified as 50 mmHg by dopamine-induced ICP reactivity (iPRx) and cerebrovascular reactivity (iCVRx) (6). The apparent lower critical CPP at high ICP was attributable to a transition from normal capillary to microvascular shunt (MVS) flow as previously hypothesized (14).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Recent studies indicate that the CBF response to a sustained decrease in CPP caused by a decrease in arterial blood pressure (ABP) or an increase in ICP has key physiological differences. [12][13][14] For example, Bragin et al 12,13 measured the cerebral haemodynamic response to sustained decrements of CPP (30 minutes at each level of ICP) and found when the decrease in CPP was brought about by an increased ICP, the lower limit of autoregulation was around 30 mm Hg, whereas with decreases in CPP brought about by a decreased ABP, the lower limit of autoregulation was around 50 mm Hg.…”
Section: Introductionmentioning
confidence: 99%